Differential Association of Wheat and Rice Consumption With Overweight/Obesity in Chinese Adults: China Health and Nutrition Survey 1991–2015 - Zhang, Jiguo; Wang, Zhihong; Du, Wenwen; Huang, Feifei; Zhang, Bing; Wang, Huijun (Frontiers in Nutrition, 2022)
Wheat and rice are main staple foods in China and likely have a major influence on health. This analysis examined the potential association between wheat and rice consumption and the risk of overweight/obesity in Chinese adults. We used data collected in the China Health and Nutrition Survey (CHNS) from 1991 to 2015. Adults aged 18–80 years old (n=11503) were included in the present analysis, for whom questionnaires and anthropometric data were collected during at least two waves. We constructed three-level mixed-effect linear regression models to estimate Body Mass Index (BMI) in relation to wheat and rice intakes and performed three-level mixed-effect logistic regression models to assess the risk of overweight/obesity. Women showed significant BMI increases of 0.14 (95% CI: 0.04, 0.24) from a higher intake of wheat but not from a higher intake of rice when adjusted for all potential confounders. Comparing the highest quartiles of intake of wheat with non-consumers in men and women, ORs (95% CI) of overweight/obesity were 1.45 (1.15, 1.85) and 1.26 (1.00, 1.60), respectively. In men there was an inverse association with risk of overweight/obesity in the comparison of the highest quartiles of intake of rice (OR: 0.73; 95% CI: 0.55, 0.96) and non-consumers when adjusted for all potential confounders. Higher intake of wheat was positively associated with the risk of overweight/obesity among Chinese adults. Further, there was an inverse association between rice intake with overweight/obesity in Chinese men but not in women.